Política, repressão e nacionalismo : o cotidiano da comunidade alemã do Vale do Iguaçu durante a Era Vargas - Dudek, Wanilton (2013)
The study of the political and social structures of the everyday is related to the comprehension of the phenomena that links the public institutions of the State to the field of the private life, establishing new power relations. The main objective of this research is to analyse how Getulio Vargas nationalist policy has changed the routine of the region of Iguaçu Valley, emphasizing the public actions directed to the German community, and how the civil population has acted in this process.In order to reach the objectives, the following resources were utilized: "O Comércio" journal clippings - which used to circulate in the region of União da Vitória and Porto União available in the current newsroom; and documents of the former Department of Political and Social Order of the states of Paraná and Santa Catarina, divided by files and themes in the Public File of Paraná. Through these sources, it was possible to observe the policing which, by means of legalized actions by the New State legislation, besides civil society involvement, systematized a surveillance policy for the German immigrants and their descendants.